PROGRAM APLIKASI INVENTORI PADA UD USAHA JAYA MANDIRI - Billy Dewantara; Ery Dewayani; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2019)
UD Usaha Mandiri is a store that located in Tanjung Pinang city which is engaged in selling furniture and raw materials for making sofas. UD Usaha Jaya Mandiri has the potential for miscalculating goods, so there are excesses and shortages of goods, especially raw materials for making sofas. The purpose of "Inventory Application Program at UD Usaha Jaya Mandiri" is to reduce the risk of losing data, print reports in and out of goods and make it easier to know the stock of goods. The method used to obtain data requirements is the observation method and the interview method. Software system design methods are used System Development Life Cycle (SDLC) and the programming language used for making programs is PHP and for manage databases using PhpMyAdmin.